2020
DOI: 10.1111/jgs.16327
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Hospitalized for Pneumonia in the United States: Incidence, Epidemiology, and Outcomes

Abstract: OBJECTIVES: To define the current incidence, epidemiology, and mortality of older adult patients hospitalized with community-acquired pneumonia (CAP) in Louisville, KY and thus estimate the burden of CAP in the older adult population of the United States. To define risk factors associated with early and late outcomes. DESIGN: This was a secondary analysis of older adults (aged ≥65 years) from the University of Louisville Pneumonia Study, a prospective population-based cohort study of all hospitalized adults wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Given that majority of elderly patients have multiple co-morbidities that increases their risk for pneumonia, this study showed that most of elderly admitted have diabetes, renal disease, heart failure as well as pulmonary tuberculosis and hypertension similar to other studies [4,12,14,19,[21][22][23]. Among numerous underlying conditions evaluated, the study showed that renal disease has an increased risk for mortality among elderly with community acquired pneumonia.…”
Section: Discussionsupporting
confidence: 81%
“…Given that majority of elderly patients have multiple co-morbidities that increases their risk for pneumonia, this study showed that most of elderly admitted have diabetes, renal disease, heart failure as well as pulmonary tuberculosis and hypertension similar to other studies [4,12,14,19,[21][22][23]. Among numerous underlying conditions evaluated, the study showed that renal disease has an increased risk for mortality among elderly with community acquired pneumonia.…”
Section: Discussionsupporting
confidence: 81%
“…1 , 2 Nearly 1 million older adults are hospitalized each year for community-acquired pneumonia, and more than one-third die within a year. 3 Pneumonia is also a common reason for hospital readmission, particularly among older adults, who often experience a functional decline during the index admission. 4 , 5 , 6 , 7 , 8 Studies have identified an inverse association between functional status and risk of hospital readmission.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies are performed in hospitals, which are based on a selected population. (8)(9)(10) Estimates on the incidence rates of infections are needed to assess the burden of disease in the community. This knowledge can serve as an information base for adapting health service delivery to an aging population.…”
mentioning
confidence: 99%